Urine Protein SDS-PAGE Reveals Different Profiles in Iraqi Children with Kala-azar - Yassir MK Al-Mulla Hummadi (College of Pharmacy University of Baghdad, 2017)
Urine proteomics have been an area of interest and recently in Kala-azar as an alternative sample type for serum or plasma. Because of simplicity, noninvasiveness of collection and simpler matrix.  Many studies had detected an increased protein excretion in the urine of patients with active Kala-azar due to renal involvement particularly by an immunological related mechanism(s). This study have demonstrated the presence of three different protein profiles in Iraqi children (Patients: including 60 children aged 4-60 months) with defined Kala-azar using the conventional SDS-PAGE on urine samples. Urine protein profile in Kala-azar patients revealed three groups of banding patterns: group-1(33.4)% of the patients show the pattern of 5 bands with a MW. Ranged (512.861-158.489), groups-2, 3 were (55, 11.6) % of the patients showing 2 banding proteins with a MW. ranged (512.861-199.526) , (199.526-181.97) respectively. These findings may be correlated with other epidemiological studies that revealed the presence of different clinical presentations like fever, spleenomegally, hepatomegally, thrombocytopaenia, and different response to leishmania therapy. Furthermore, the presence of different protein patterns may also be related to the chronicity of infection and the degree of renal involvement.  The presence of a similar protein band between group-1 and 2 may be of diagnostic purpose and further studies on expanded number of patients are required to identify that kind of protein or other urine protein profiles.  Key words: Protein band, protein pattern, sodium dodecyl sulphate-poly acrylamide gel electrophoresis (SDS-PAGE), urine proteome, visceral leishmaniasis.